Synthesis and pharmacological investigation of novel 4-(3-ethylphenyl)-1-substituted-4H-[1,2,4]triazolo[4,3-a]quinazolin-5-ones as a new class of H1-antihistaminic agents - Alagarsamy, Veerachamy (Array, 2009)
Ciklizacijom 3-(3-etilfenil)-2-hidrazino-3H-kinazolin-4-ona (3) s različitim donorima jednog C atoma sintetizirana je serija novih 4-(3-etilfenil)-1-supstituiranih 4H-[1,2,4]triazolo[4,3-a]kinazolin-5-ona (4a-j)